Rationally designed rare earth separation by selective oxalate solubilization. Issue 77 (3rd September 2020) - Prodius, Denis; Klocke, Matthew; Smetana, Volodymyr; Alammar, Tarek; Perez Garcia, Marilu; Windus, Theresa L.; Nlebedim, Ikenna C.; Mudring, Anja-Verena
Abstract : A simple, eco-friendly and efficient chemical separation of rare earth oxalates (CSEREOX) in water within two rare earth metals subgroups has been elaborated. Abstract : A simple, environmentally benign, and efficient chemical separation of rare earth oxalates (CSEREOX) within two rare earth element (REE) subgroups has been developed. The protocol allows for selective solubilization of water-insoluble oxalates of rare earth elements, and results in efficient REE extraction even at low initial concentrations (<5%) from processed magnet wastes.